Analysis of students' learning interests in social studies subjects: a case study at SMPN 9 - Viola; Ajeng Priska Sari; July Pangaribuan; Rachel Maulina Pasaribu; Desri Rut Hartati Nadeak5 (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze and identify internal and external factors that affect students' interest in learning social studies subjects at SMPN 9 Medan in grade VIII. The method used is qualitative research with a case study approach. The case study approach was chosen because this research focuses on one case that is contextual and in-depth, namely regarding students' learning interests in social studies subjects in Class VIII. Data collection was carried out through observation, interviews and document study techniques. The results of the analysis show that students' interest in learning social studies subjects at SMPN 9 Medan in grade VIII is still relatively low. This is shown by the active participation of students who are low in learning, not focused, students are passive and easily distracted by class conditions. In addition, this study found that students' emotional conditions also affect their interest and participation in learning. The findings of this study show the need to develop more varied social studies learning, conducive classroom management and an approach that pays attention to students' emotional states so that students' interest and involvement in the learning process can increase.